Examining Factors Influencing Antenatal Care Visits in Nigeria - Bamigbala, Olateju Alao; Odey, Solomon Etia; Ojetunde, Ayodeji Oluwatobi; Ikrimat, Aliyu; ThankGod, Joshua (Darul Yasin Al Sys, 2025)
The number of maternal deaths worldwide linked to pregnancy and childbirth is high in Nigeria. Meanwhile, attending the recommended number of antenatal care (ANC) appointments may help reduce maternal morbidity and death. This research sought to examine the factors influencing ANC visits in Nigeria. This study employed secondary data extracted from the Nigeria Demographic and Health Survey 2018. A total sample of 21,427 women was included. Data analysis was carried out using the Zero-Inflated Negative Binomial Regression. The level of significance was p < 0.05. Among the participants, 5,337 (24.9%) did not attend any ANC visits. As the number of visits increases, there is a gradual decrease in frequency, with 4 visits being the most common (12.7%). Findings revealed that place of residence, maternal education, insurance coverage, marital status, partner’s education, region, and age of the mother consistently impacted additional ANC visits. While the place of residence, maternal education, insurance coverage, partner’s education, region, and age of the mother impacted zero ANC visits. Policymakers should focus on rural areas and those with lower education levels to improve ANC visits. Furthermore, specific attention should be given to pregnant women over 18 years of age to ensure they receive adequate ANC.